2020
DOI: 10.1161/circresaha.120.316742
|View full text |Cite
|
Sign up to set email alerts
|

JAM-A Acts via C/EBP-α to Promote Claudin-5 Expression and Enhance Endothelial Barrier Function

Abstract: Rationale: Intercellular tight junctions are crucial for correct regulation of the endothelial barrier. Their composition and integrity are affected in pathological contexts, such as inflammation and tumour growth. 'Junctional adhesion molecule-A' (JAM-A) is a transmembrane component of tight junctions with a role in maintenance of endothelial barrier function, although how this is accomplished remains elusive. Objective: We aimed to understand the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 76 publications
1
68
0
Order By: Relevance
“…ATF4 functions in heterodimers with other bZIP TFs and also co-regulates many of its target genes together with other TFs ( Kilberg et al., 2009 ). Many of those bZIP TFs, such as cMYC ( Wilhelm et al., 2016 ), C/EBP ( Kakogiannos et al., 2020 ; Loinard et al., 2012 ; Min et al., 2017 ), JunD ( Gerald et al., 2004 ), and others ( Hamik et al., 2006 ), have been linked to endothelial biology before. Also, ATF3/4 have been previously shown to stabilize P53 ( Yan et al., 2005 ), a known regulator of angiogenesis ( Gogiraju et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 functions in heterodimers with other bZIP TFs and also co-regulates many of its target genes together with other TFs ( Kilberg et al., 2009 ). Many of those bZIP TFs, such as cMYC ( Wilhelm et al., 2016 ), C/EBP ( Kakogiannos et al., 2020 ; Loinard et al., 2012 ; Min et al., 2017 ), JunD ( Gerald et al., 2004 ), and others ( Hamik et al., 2006 ), have been linked to endothelial biology before. Also, ATF3/4 have been previously shown to stabilize P53 ( Yan et al., 2005 ), a known regulator of angiogenesis ( Gogiraju et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…76 Recently, it was found that JAM-A acts through activation of the cAMP-regulated guanine nucleotide exchange factor I to up-regulate the expression of claudin-5 and limit vascular permeability. 77 In the setting of cerebral inflammation, JAM-A relocalizes to the endothelial apical membrane and promotes leukocyte adhesion. 78 Endothelial cells also express adherens junctions that contain transmembrane proteins, cadherins, of which VEcadherin is most important for adhesion between cells.…”
Section: Blood-brain Barriermentioning
confidence: 99%
“…In this sense, the CLDN5–ERα signaling loop may be attributed to the recent finding showing that a weak association of the CLDN5 variant rs10314 with schizophrenia only in female subjects of 22q11.2 DS (Guo et al, 2020). As other transcription factors, such as SOX18 and CCAAT/enhancer‐binding proteinα (C/EBPα), are also known to induce CLDN5 expression (Fontijn et al, 2008; Kakogiannos et al, 2020; Roudnicky et al, 2020), it would be intriguing to validate whether the positive CLDN5–SOX18 and CLDN5–C/EBPα signaling loop contribute to control of the region‐selective endothelial barrier.…”
Section: Main Textmentioning
confidence: 99%